2006
DOI: 10.1063/1.2196227
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion, activation, and regrowth behavior of high dose P implants in Ge

Abstract: Time evolution of the chemical profile, electrical activity, and regrowth of P implanted in Ge at a concentration above the maximum equilibrium solubility is investigated at 500°C rapid thermal annealing temperature. During the first anneal, a second, epitaxial regrowth of a part of the amorphous layer leads to P trapping in substitutional sites at a level of about 4×1020atoms∕cm3. However, nonsubstitutional P atoms frozen in the crystal at high concentration during recrystallization form large, inactive preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
66
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 17 publications
4
66
0
Order By: Relevance
“…1 Whereas a p-channel Ge-MOSFET made of heavily boron ͑B͒ doped source and drain regions have already been demonstrated, 2,3 the n-channel MOSFET remains a challenge due to the enhanced diffusion of n-type dopants under extrinsic doping conditions and the deactivation of the donors for concentrations exceeding 10 19 cm −3 . [3][4][5][6][7] The enhanced diffusion and deactivation are directly associated with the properties of the point defects involved in the diffusion mechanisms. 6,7 In the case of phosphorus ͑P͒, arsenic ͑As͒, and antimony ͑Sb͒ diffusion in Ge, the mass transport is mediated by singly negatively charged donor-vacancy pairs.…”
Section: Introductionmentioning
confidence: 99%
“…1 Whereas a p-channel Ge-MOSFET made of heavily boron ͑B͒ doped source and drain regions have already been demonstrated, 2,3 the n-channel MOSFET remains a challenge due to the enhanced diffusion of n-type dopants under extrinsic doping conditions and the deactivation of the donors for concentrations exceeding 10 19 cm −3 . [3][4][5][6][7] The enhanced diffusion and deactivation are directly associated with the properties of the point defects involved in the diffusion mechanisms. 6,7 In the case of phosphorus ͑P͒, arsenic ͑As͒, and antimony ͑Sb͒ diffusion in Ge, the mass transport is mediated by singly negatively charged donor-vacancy pairs.…”
Section: Introductionmentioning
confidence: 99%
“…2 This is particularly important for donor impurities for which activation control can be problematic. 3 In previous studies, it has been concluded that most impurities mainly occupy substitutional lattice sites in Ge and, with the exception of boron ͑B͒, dopant diffusion is mainly mediated by vacancies ͑V͒ as interstitial mechanisms typically have significantly higher activation enthalpies. 2, Aluminium ͑Al͒, gallium ͑Ga͒, indium ͑In͒, and B are acceptor atoms that can potentially be used as p-type dopants in Ge technology.…”
mentioning
confidence: 99%
“…[6][7][8][9] Quantifying the expected diffusion is difficult as available diffusivity values were either extracted under intrinsic conditions, or at higher temperatures than studied here. 1 However, extrapolating diffusivity values from Chui et al, 6 which are accurate for high concentrations, only a few nanometers of diffusion could be expected for the highest thermal budgets in this work.…”
mentioning
confidence: 99%
“…n-type dopants in germanium have proven to be problematic, and are now a key bottleneck in the realization of advanced n-type MOS ͑NMOS͒ device performance and scaling. 5 In short, phosphorus ͑P͒ and arsenic ͑As͒ are relatively difficult to activate and diffuse quickly, [6][7][8][9] leading to high resistances and limited capability to reduce the device dimensions.…”
mentioning
confidence: 99%